An Analysis of The Impact of Remixed Songs on Tik Tok Social Media on Children's Language Development In Elementary School - Gutama, Andika; Andriansyah, Ella Nur (Universitas Negeri Surabaya, 2023)
Tik Tok is an application containing short videos accompanied by music. Many songs on Tik Tok are not suitable for elementary school students to listen to, such as Mangku Purel, Abang Evil, and No Comment, so these songs have an impact on children's language development. This research aims to determine the impact of songs on Tik Tok social media on children's language development in elementary school. This type of research is qualitative descriptive research. The objects of this research are teachers and students. The data collection procedures used were observation, interviews and documentation. From the research carried out, the following results were obtained: there are many negative impacts, such as students playing with cellphones more, the songs consumed by students are not suitable for elementary school-age children, the videos on Tik Tok are not all positive, Tik Tok affects language development and environment, students follow language like adults and students cannot differentiate between positive and negative. Based on the results of research that has been carried out, there are many negative impacts, (1) Playing with cellphones more. (2) The songs consumed are not suitable for elementary school-age children. (3) Not all of the videos on Tik Tok are positive, (4) Tik Tok influences language development and the environment, (5) Students follow the language like adults from the Tik Tok application, (6) Students cannot yet differentiate between what is good and what is not good. This has a big impact on children's language development, apart from being used as a means of entertainment, a lot of content is accompanied by songs that are not suitable for elementary school-age children. Therefore, parents need to play a role in using social media, so that children's language does not influence Tik Tok language.